Biondicators. Tools for the impact assessment of aquaculture activities on the marine communities - Giménez Casalduero F. (Environmental impact assessment of Mediterranean aquaculture farms, 2001)
The use biotic indicators for the assessment of the impact of organic pollution is a very common monitoring technique. The present paper presents detailed information about the different types of biological indicators (physiology and immunology bio-indicators, indicators species and biological pollution indices), which can be based on indicator species, on trophic strategies, on the structural heterogeneity, or those incorporating biomass. All these tools can help us to interpret the state of a community and the possible changes due to certain environmental pressure. The combined use of different environmental descriptors makes it possible to identify various parameters that are capable of determining the area of impact.
TECAM Seminar on Environmental Impact Assessment of Mediterranean Aquaculture Farms, 2000/01/17-21, Zaragoza (Spain)